Initial Findings of a Multicomponent School Health Intervention in Rural Appalachia: The Greenbrier CHOICES Project. (April 2020) - Jones, Emily; Zuest, Luciana; Bulger, Sean; Elliott, Eloise; Cho, Kibum; Lilly, Christa
Background . Schools are an important setting for health promotion because they afford children and adolescents numerous opportunities to accumulate the recommended physical activity (PA) minutes and make other health-related decisions, including healthy eating. Unfortunately, there is little evidence of coordinated school-based health interventions in rural Appalachia. The Greenbrier Children's Health Opportunities Involving Coordinated Efforts in Schools Project was a federally funded, 3-year, multicomponent school-based health intervention focused on PA, healthy eating, and weight management. Aims . The purpose of this study was to evaluate the impact of Greenbrier Children's Health Opportunities Involving Coordinated Efforts in Schools on adolescent PA, dietary behaviors, and weight status. Method . Measures of PA, dietary behaviors, and body mass index were collected across 14 data points throughout the intervention (including a baseline in Year 1). Results . Participants included 4, 633 randomly selected middle school students ( M = 2, 289, F = 2, 344) across the intervention. Baseline to Year 3 findings revealed a 12.8 percentage point increase in students achieving 60 minutes of daily PA. There were no significant differences in either dietary behavior or body mass index. Discussion . Findings provide evidence of the positive impact comprehensive school-based health interventions can have on middle school student health-related behaviors. Conclusion . Schools remain an ideal setting for health promotion. Initiatives targeting more than one level of influence on health-related behaviors are more likely to succeed.